Wyłącz przed nawias jednomian 2x .
a) 2x-2xy
b) 4x-8xy
c) 6x2 -12x
( 6x2 = 6xkwadrat )

Przedstaw w postaci iloczynu .
a) 5x2 - 15x
b)6by - 6b
c) -8xy + 8x
d)10a2 - 2ab
e)xy -x2y
f)6a -24b +30c
g)12ab2 + 16b2
h)x3 -2x2 +x
i)2xy +3x -x2y

< w podpunktach a) d) e) g) h) i) 2 przy jednomianach oznacza kwadrat ;-)) >

3

Odpowiedzi

2010-02-21T17:19:37+01:00
1
a) 2x(1-y)
b) 2x(2-4y)
c) 2x(3x-6)

2
a) 5x(x -3)
b) 6b(y-1)
c) 8x(-y+1)
d) 2a(5a -b)
e) xy(1-x)
f) 6(a-4b+5c)
g) 4b2(3a+4)
h) x(x2-2x+1)
i) x(2y+3+xy)
2 5 2
  • Użytkownik Zadane
2010-02-21T17:21:24+01:00
Wyłącz przed nawias jednomian 2x .
a) 2x-2xy =2x(1-y)
b) 4x-8xy=2x(2-4y)
c) 6x2 -12x=2x(3x-6)
( 6x2 = 6xkwadrat )

Przedstaw w postaci iloczynu .
a) 5x2 - 15x=5x(x-3)
b)6by - 6b=6b(y-1)
c) -8xy + 8x= 8x(-y+1)
d)10a2 - 2ab= 2a(5a-b)
e)xy -x2y=xy(1-x)
f)6a -24b +30c=6(a-4b+5c)
g)12ab2 + 16b2=4b2(3a+4)
h)x3 -2x2 +x=x(x2-2x+1)
i)2xy +3x -x2y=x(2y+3-xy)

< w podpunktach a) d) e) g) h) i) 2 przy jednomianach oznacza kwadrat ;-)) >
2 5 2
Najlepsza Odpowiedź!
2010-02-21T17:22:36+01:00
Wyłącz przed nawias jednomian 2x .
a) 2x-2xy=2x(1-y)
b) 4x-8xy=2x(2-4y)
c) 6x² -12x=2x(3x-6)
Przedstaw w postaci iloczynu .
a) 5x² - 15x=5x(x-3)
b)6by - 6b=6b(y-1)
c) -8xy + 8x=-8x(y-1)
d)10a² - 2ab=2a(5a-b)
e)xy -x²y=xy(1-x)
f)6a -24b +30c=6(a-4b+5c)
g)12ab² + 16b²=4b²(3a+4)
h)x³ -2x² +x=x(x²-2+1)=x(x-1)²
i)2xy +3x -x²y=x(2y+3-xy)

prosze:)
7 4 7